Environmental innovation and employment dynamics in different technology fields: An analysis based on the German community innovation survey 2009 - Jens Horbach; Klaus Rennings (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
The employment effects of environmental technologies are in the focus of politicians but there are only few studies analyzing these effects for different environmental innovation fields. We use the 2009 wave of the German part of the Community Innovation Panel (CIS) allowing for such an analysis at the firm level. The main focus of the paper lies on the analysis of the adaptation behavior of firms with respect to the relationship of employment and (environmental) innovation. We use an endogenous switching regression approach to take the simultaneous haracter of innovation activities and employment demand into consideration. Our econometric analysis shows that innovative firms in general are characterized by a significantly more dynamic employment development. Especially the realization of environmental process innovations leads to a higher employment within the firm. The theoretical background of this finding is that process innovation induced cost savings improve the competitiveness of firms. This has a positive effect on demand and thus also increases employment. A more detailed analysis by different environmental innovation fields shows that material and energy savings are positively correlated to employment because they especially help to increase the profitability and competitiveness of the firm. On the other side, air and water process innovations that are still dominated by end-of-pipe technologies have a negative impact on the employment development.
Keywords: Q52; Q55; J49; C25; 330; Employment; Environmental Innovation; Innovation Behaviour